Inflammation Is Associated with Voriconazole Trough Concentrations - van Wanrooy, Marjolijn J. P. (Antimicrob Agents Chemother, 2014)
Voriconazole concentrations display a large variability, which cannot completely be explained by known factors. Inflammation may be a contributing factor, as inflammatory stimuli can change the activities and expression levels of cytochrome P450 isoenzymes. We explored the correlation between inflammation, reflected by C-reactive protein (CRP) concentrations, and voriconazole trough concentrations. A retrospective chart review of patients with at least one steady-state voriconazole trough concentration and a CRP concentration measured on the same day was performed. A total of 128 patients were included. A significantly (P < 0.001) higher voriconazole trough concentration was observed in patients with severe inflammation (6.2 mg/liter; interquartile range [IQR], 3.4 to 8.7 mg/liter; n = 20) than in patients with moderate inflammation (3.4 mg/liter; IQR, 1.6 to 5.4 mg/liter; n = 60) and in patients with no to mild inflammation (1.6 mg/liter; IQR, 0.8 to 3.0 mg/liter; n = 48). The patients in all three groups received similar voriconazole doses based on mg/kg body weight (P = 0.368). Linear regression analyses, both unadjusted and adjusted for covariates of gender, age, dose, route of administration, liver enzymes, and interacting coadministered medications, showed a significant association between voriconazole and CRP concentration (P < 0.001). For every 1-mg/liter increase in the CRP concentration, the voriconazole trough concentration increased by 0.015 mg/liter (unadjusted 95% confidence interval [CI], 0.011 to 0.020 mg/liter; adjusted 95% CI, 0.011 to 0.019 mg/liter). Inflammation, reflected by the C-reactive protein concentration, is associated with voriconazole trough concentrations. Further research is necessary to assess if taking the inflammatory status of a patient into account is helpful in therapeutic drug monitoring of voriconazole to maintain concentrations in the therapeutic window, thereby possibly preventing suboptimal treatment or adverse events.